Efektivitas Pembelajaran Daring Menggunakan Multimedia Pada Mata Pelajaran PAI Kelas XII SMA Negeri 1 Banuhampu - Rahma Putri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
This research was motivated by the initial system of online learning using multimedia in the form of printed books or power points which made students less understanding of learning so that student learning outcomes were not satisfactory. Based on the data of grade XII students. Social Studies 2 in PAI subjects at SMA Negeri 1 Banuhampu the average value of students using multimedia in the form of printed books and powerpoints is 71.97 with a percentage of 55.2% of students who did not complete and 44.8% declared complete with completeness limits (KKM). ) 75. The purpose of this study was to find out how the online learning outcomes of students before and after using multimedia in the form of videos and to find out whether after using multimedia in the form of videos were more effective than before using multimedia in the form of videos in PAI subjects for class XII.IPS 2 students in SMA State 1 Banuhampu. The research used a descriptive quantitative approach. Descriptive, namely to describe or describe the results of online learning before and after using multimedia in the form of videos in PAI subjects for class XII IPS 2 SMA Negeri 1 Banuhampu students. The population in this study were all students of class XII at SMA Negeri 1 Banuhampu. The sampling used in this research is purposive sampling, the determination of the sample size with certain considerations. The data were collected from the daily test scores of XII.IPS class students 2. The data analysis technique used the mean (average) formula, the level of effectiveness, categorizing the data, testing the hypothesis with the T one sample test. Based on the results of data analysis and discussion of research results, it can be concluded that the average value of class XII.IPS 2 students using multimedia in the form of videos in PAI subjects is 83.41 with the lowest score being 73 while the highest score is 97, for the highest score ( mode) which is 85 totaling 9 students. From the results of the data category scores, the value of online learning using multimedia in the form of videos in PAI subjects for class XII students. Social Studies 2 can be said to be in the medium category because as many as 12 students are in the medium category. The results of the hypothesis test using the T one sample test, it is known that the significance of the value of tcount > ttable is 2.862 > 2.048 with a degree of freedom (df) of 28. From the results of sig (2 tailed) which is 0.008 < 0.05 then ha is accepted and h0 is rejected with an average decision The average value of online learning using multimedia in the form of videos is above 80. Therefore, online learning using multimedia in the form of videos is effective in PAI subjects for class XII students of SMA Negeri 1 Banuhampu.